Establishing a new staging system for oral submucous fibrosis and correlation of the proposed staging system to traditional histopathological grading: A clinico-histopathological study - Shaul Hameed K.; Laxmikant Chatra; Prashanth Shenai (Elsevier, 2019)
Background & objectives: Oral submucous fibrosis (OSF) is a potentially malignant disorder of the oral cavity leading to reduction in mouth opening. Mouth opening assessment is used as one of the methods to assess the severity of the disease. In this study the normal maximum mouth-opening capacity of an individual is considered in assessing the reduction in mouth opening. This study was done to establish a new clinical staging pattern in OSF and to evaluate the relationship between the proposed staging system and traditional histopathological grading system of OSF. Materials and methods: The study included 50 clinically diagnosed OSF patients. Normal mouth opening was established by measuring three-finger index (TFI). Existing maximum mouth opening was established by measuring the interincisal distance. Presence of palpable vertical bands was recorded. Histopathological grading was done according to Pindborg and Sirsat. Percentage of reduction in mouth opening (PRMO) was calculated and the mean of PRMO in different clinical and histopathological stages was analysed by fisherman's extract test. A new staging pattern for OSF was proposed from the data. Results: PRMO was assessed at different clinical stages. A range between 16% and 47% was obtained, and statistically the p value of <0.001 was very highly significant. Similarly, a range between 17% and 45.6% was obtained when PRMO was assessed at different histopathological grading; again the statistical value was very highly significant with a p value of <0.001. Conclusion: With the data obtained from our study, the following clinical staging pattern can be adapted: stage I indicates that the PRMO is <30%, Stage II between 30-45%, and stage III >45%. Hence it may be appropriate to asses the disease severity and stage by assessing the degree of disability (i.e., mouth opening reduction considering the individual normal mouth opening ability). The determination of PRMO may be a useful tool in this direction. Keywords: Maximum mouth opening, Three finger index, Percentage of reduction in mouth opening, Vernier caliper, Grading of oral submucous fibrosis